Integration of forward osmosis process and a continuous airlift nitrifying bioreactor containing PVA/alginate-immobilized cells - Jeong, Dawoon; Cho, Kyungjin; Lee, Chang-Ha; Lee, Seockheon; Bae, Hyokwan (ELSEVIER SCIENCE SA, 2016)
Forward osmosis (FO) and biological nitrification processes were integrated in this study. High strength ammonia wastewater of 2500 mg-N/L was partially nitrified at an ammonia conversion rate of 1.34 +/- 0.25 kg-N/m(3)-d under the limitation of an acidification buffer, i.e., HCO3--C/NH4+-N = 1, as a control factor. Direct contact between biomass and a cellulose triacetate FO membrane was avoided by employing PVA/alginate-immobilized nitrifiers in the bioreactor. The simultaneous FO process concentrated the wastewater at concentration factors (CFs) of up to 2.34 during the partial nitritation (PN) reaction. As a result, the concentration of total dissolved solids (TDS) ranged from 13.6 g/L to 35.7 g/L. It was found that salinity higher than 17 g-TDS/1. inhibited the activity of the nitrite-oxidizing bacteria, but not the ammonia-oxidizing bacteria. Scanning electron microscopy and fluorescence excitation emission matrix and liquid chromatography-organic carbon detection analysis revealed the existence of hydrophilic organic fouling including biopolymers and low molecular weight neutrals on the surface of the FO active layer. However, the FO fouling was successfully controlled by air scouring for 15 min. (C) 2016 Elsevier B.V. All rights reserved.